(untitled) (American Journal of Islam and Society, 2003)
This book, an historical survey of the Islamic injunction to command right and forbid wrong, a biographical exposé of Muslims who understood and practiced this principle, and a bibliographical reference, is a welcome and timely addition to the literature on Islamic thought. Detailed and extensive, yet not particularly difficult to read, it is equally accessible to all readers. Its main theme is the basic Islamic individual and communal duty to stop other people from doing wrong. Cook contends that few cultures have paid such meticulous concern to this matter, despite the issue’s intelligibility in just about any culture. As a central Islamic tenet, this principle could not be ignored, and yet its sociopolitical implications and consequences made it the focus of rigorous attention by Muslim scholars. The doctrine inexorably brings up the balancing and equally sacrosanct value of privacy, together with issues of knowledge, specialization, competence, and stability – the “how” of the whole matter. After all, the act of forbidding wrong was not supposed to undermine the principle by becoming an intrusive breach of privacy, an excursus into social prying, or a potential justification for unmitigated rebellion against the state. The book consists of five parts comprising 20 chapters. Part I sets the descriptive framework by elaborating the normative material found in the Qur’an, Qur’anic exegesis, tradition, and biographical literature about early Muslims. Part II is dedicated to the Hanbali school ince its foundation by Ahmad ibn Hanbal (d. 241/855) in Baghdad. The author traces its shifting influences in Damascus and Najd, where the school continues to have a hold in the Saudi state to this day. Part III deals with the Mu‘tazilis and their Zaydi and Imami heirs, all of which, Cook contends, provide the richest documentation for the intellectual history of forbidding wrong. The remaining Sunni schools of thought, the Khariji Ibadis, together with a chapter on al-Ghazali’s tackling of the duty and another chapter pulling together the discussion of classical Islam, comprise Part IV. Finally, Part V surveys the duty’s salience in modern Islamic thought and developments in both the Sunni and Imami schools and engages in a comparative exercise with this duty’s pre-Islamic antecedents and with non-Islamic cultures, including the modern West ...